Extensible Web: An XML-view based web engineering methodology - Rajugan, R.; Gardner, W.; Chang, Elizabeth; Dillon, Tharam S. (Springer-Verlag, 2005)
XML is becoming increasingly a popular medium in industrial informatics for (a) storing and representing unstructured and semi-structured information such as web content and (b) messaging between heterogeneous data sources. For both these purposes it is important to provide a high level, model driven solution to design and implement websites that are capable of handling heterogonous schemas and documents. For this, we need a methodology, that provides higher level of abstraction of the domain in question (here the web) with rigorously defined standards that are to be more widely understood by all stakeholders of the system. To achieve this, in this paper, we propose an XMLview driven design and architecture solution (methodology) for web engineering called xWeb. This methodology uses Object-Oriented (OO) conceptual modelling techniques in combination with proven higher-level web user interface engineering and data engineering techniques that provides a comprehensive, yet generic web design methodology. Also, xWeb architecture utilizes XML technologies without requirements for a middleware and provides support for web portals.